Fair division with general equilibrium effects and international climate politics - Christoph Böhringer; Carsten Helm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper introduces a solution for the fair division of common property resources in production economies with multiple inputs and outputs. It is derived from complementing the Walrasian solution by welfare bounds, whose ethical justification rests on commonality of ownership. We then apply this solution to the question of burden sharing in the climate change regime, using an intertemporal computable general equilibrium model. For a wide range of initial allocations of CO2 emission rights, we find that developing countries should participate in emission reduction efforts in order to increase their global efficiency, but should also be fully compensated for their incremental abatement costs.
Keywords: Q20; D63; D58; 330; Fair division; climate change; common property resources; welfare bounds; CGE models; Allmenderessource; Gerechtigkeit; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Klimaschutz; Kohlendioxid; Emissionsrechte; Theorie; Welt